The Converted War Canoe: Cannibal Raiders, Missionaries and "Pax Britannica" on Dobu Island, Papua New Guinea - Keuhling, Susanne (Anthropologica, 2015)
This article examines an historic event of peacemaking: the moment in which warfare was given up by the Dobu Islanders of Papua New Guinea. I provide a larger context of the event by combining the detailed historical sources with local memories and ethnographic detail from my fieldwork over 20 years. This lets me compare three notions of peace: the systemic view of the colonial authority, the spiritual perspective of the missionaries, and the temporal and superficial peace of Dobu Islanders. Framed by newly emerging power relations, the event reminds us that peace is a complex concept that needs more theorizing.